Replication and resolution of cloned poxvirus telomeres in vivo generates linear minichromosomes with intact viral hairpin termini. - DeLange, A M (1986)
The covalently closed terminal hairpins of the linear duplex-DNA genomes of the orthopoxvirus vaccinia and the leporipoxvirus Shope fibroma virus (SFV) have been cloned as imperfect palindromes within circular plasmids in yeast cells and recombination-deficient Escherichia coli. The viral telomeres inserted within these recombinant plasmids are equivalent to the inverted-repeat structures detected as telomeric replicative intermediates during poxvirus replication in vivo. Although the telomeres of vaccinia and SFV show little sequence homology, the termini from both viral genomes exist as AT-rich terminal hairpins with extrahelical bases and alternate "flip-flop" configurations. Using an in vivo replication assay in which circular plasmid DNA was transfected into poxvirus-infected cells, we demonstrated the efficient replication and resolution of the cloned imperfect palindromes to bona fide hairpin termini. The resulting linear minichromosomes, which were readily purified from transfected cells, were shown by restriction enzyme mapping and by electron microscopy to have intact covalently closed hairpin termini at both ends. In addition, staggered unidirectional deletion derivatives of both the cloned vaccinia and SFV telomeric palindromes localized an approximately 200-base-pair DNA region in which the sequence organization was highly conserved and which was necessary for the resolution event. These data suggest a conserved mechanism of the resolution of poxvirus telomeres.